Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1116/1.582300
|View full text |Cite
|
Sign up to set email alerts
|

Channeling effects during focused-ion-beam micromachining of copper

Abstract: The rapid introduction of copper metallization for semiconductor devices has prompted increased research into focused-ion-beam micromachining of copper. Studies with the aim of increasing the material removal rate of Cu by focused-ion-beam micromachining have been complicated by variable micromachining behavior apparently resulting from differing Cu film morphologies produced by the various Cu deposition procedures. This work examined the micromachining behavior of thin copper films produced by physical-vapor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Focused ion beam (FIB) milling (Phillips et al 2000;Gonzalez et al 2001;Tseng 2005) has been employed for fabricating nanostructures used in a wide variety of products including nano-cavity lasers, photonic crystals, as well as chemical and biological sensors based on sub-wavelength aperture arrays. In this work, we employed FIB milling for gold nanopillar formation on planar substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Focused ion beam (FIB) milling (Phillips et al 2000;Gonzalez et al 2001;Tseng 2005) has been employed for fabricating nanostructures used in a wide variety of products including nano-cavity lasers, photonic crystals, as well as chemical and biological sensors based on sub-wavelength aperture arrays. In this work, we employed FIB milling for gold nanopillar formation on planar substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Focused ion beam (FIB) milling [21][22][23] is an extremely important tool for fabrication of various types of nanostructures used in a wide variety of products including photonic crystal waveguides, nanocavity lasers, as well as chemical and biosensors based on subwavelength aperture arrays. In this work, we employed FIB milling for gold nanopillar formation on optical fiber tips and planar substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty in FIB milling of Cu has been discussed several times [1,2] and milling nonuniformities only gets worse when a low-k dielectric is in the process [3]. The purpose of this paper is to report on success in FIB editing devices with interconnects of copper, SiO 2 and low-k dielectrics.…”
Section: Introductionmentioning
confidence: 97%
“…Later it was revealed that the situation was even worse when low-k dielectrics were included in the interconnect stack [3] because those chemistries which offered help with copper over SiO 2 actually make the situation worse for copper over low-k. The lack of uniform etching was proven by P Russell's group at NCSU to be due to channeling [2]. Because of the great variation in sputter yield (up to 10x) with copper grain orientation [2], circuit edit requires a chemistry with copper selectivity relative to neighboring dielectrics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation